2019
DOI: 10.1097/dcr.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Invasion and Perineural Invasion Negatively Impact Overall Survival for Stage II Adenocarcinoma of the Colon

Abstract: BACKGROUND: Lymphovascular invasion and perineural invasion are histopathological features associated with higher-risk colon cancer. OBJECTIVE: The purpose of this study was to quantify the impact of lymphovascular and perineural invasion on overall survival after diagnosis and to determine the protective effect of adjuvant chemotherapy for early adenocarcinoma with high-risk factors. DESIGN: This was a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 26 publications
3
75
3
Order By: Relevance
“…In colorectal cancer, lymphovascular invasion is considered to be an independent predictor of poor prognosis (48)(49). It is not only associated with higher T stage and poor differentiation, but also a key link of distant metastasis, and an important risk factor for cancer recurrence and shortened survival (50)(51)(52). In this meta-analysis, we observed a higher rate of lymphovascular invasion in the SEMS group.…”
Section: Discussionmentioning
confidence: 54%
“…In colorectal cancer, lymphovascular invasion is considered to be an independent predictor of poor prognosis (48)(49). It is not only associated with higher T stage and poor differentiation, but also a key link of distant metastasis, and an important risk factor for cancer recurrence and shortened survival (50)(51)(52). In this meta-analysis, we observed a higher rate of lymphovascular invasion in the SEMS group.…”
Section: Discussionmentioning
confidence: 54%
“…12 Meanwhile, a recent study showed that PNI and LVI showed negative impacts on survival even in early-stage colon cancer. 11 Therefore, it is necessary to explore any pathological differences between patients with obstructive and nonobstructive cancer as well as between patients undergoing ES and SBTS. In the present study, Cox regression analysis showed that PNI and tumor deposit were important factors for survival.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, lymphovascular invasion (LVI) and perineural invasion (PNI) detrimentally affect the survival of patients with colon cancer. 11 A recent study found that obstruction is associated with PNI and may contribute to increased postoperative recurrence in colon cancer. 12 Therefore, it is important to further explore whether pathological factors such as LVI and PNI are associated with obstruction or stent placement.…”
Section: Introductionmentioning
confidence: 99%
“…However, overemphasis on LNM in the colon cancer TNM staging system is controversial. Many studies have reported the prognostic impact of high-risk features beyond LNM [11][12][13][14][15][16][17][18][19][20][21][22][23]. One study showed the relationship between the number of high-risk features and prognosis, demonstrating that 5-year OS rate was less than 20% in patients with stage II colon cancer with four or more high-risk features [18].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, based on the fact that the vascular system does not have a gateway like LN, we hypothesized that the tumor cells would spread through the vascular channel more aggressively and faster than through the lymphatic system. Several studies have shown that VI is a poor prognostic factor in colon cancer [11][12][13][14]. However, there were few studies that compared the prognostic impact of VI and LNM.…”
Section: Introductionmentioning
confidence: 99%